DARI PESANTREN UNTUK NEGERI: KIPRAH KEBANGSAAN KH. HASYIM ASY’ARI - Fadli, Muhammad Rijal; Miftahuddin, Miftahuddin (JURNAL ISLAM NUSANTARA, 2019)
This study present KH. Hasyim Asy'ari's nationality, which has a great service to the Indonesian people. Since childhood, KH. Hasyim Asy'ari is a typical santri who likes to travel to seek knowledge in various pesantren, both in the archipelago and in Mecca. After returning from Mecca, KH. Hasyim Asy'ari founded Pesantren Tebuireng and established the Nahdlatul Ulama organization. Its work began to stand out when it declared the fatwa of jihad against the Dutch colonialists. The national jihad declared by KH. Hasyim Asy'ari, proved to be very effective in burning the spirit of muslims patriotism in Indonesia, so that the colonizers could be eliminated from the country. During the Dutch colonial period, KH. Hasyim Asy'ari was attacked by the Dutch and his pesantren was also burned. Whereas in the Japanese period, KH. Hasyim Asy'ari was arrested and jailed for opposing Japanese orders and policies, Seikerei.